A new approach for an ultra-thin piezoresistive sensor based on solidified carbon ink film - Ying Yi (438810) (2020)
Conventional flexible piezoresistive strain sensors that use conductive particles polymer composites exhibit thick structures with a low sensitivity to external tension. This paper presents a cost-effective method to fabricate ultra-thin and highly sensitive piezoresistive strain sensors. In our fabrication steps, carbon ink that is mainly composed of carbon black particles is solidified with a drying process to form a “paperlike,” flexible conductive film. Without any surface modification techniques, the carbon ink film is directly placed onto liquid-state PDMS and then bonded after the drying process. Following the rapid prototyping, different performance metrics of the fabricated sensors, including piezoresistivity, gauge factor, temperature dependency, elastic modulus, and repeatability are measured. Specifically, sensors fabricated with this method show a significantly improved gauge factor (~26) compared to similar flexible sensors fabricated by more complicated micro-fabrication methods. The proposed method of fabrication and the corresponding ultra-thin (~45 μm) sensor prototype may benefit the design and mass production of future wearable biomedical and healthcare sensors. Other Information Published in: Journal of Materials Science License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10853-020-05309-8